The Effect of a health belief model based education program to prevent diabetes complications on dietary behaviors of Indonesia adults with type 2 diabetes mellitus - Yesi Hasneli Nazir (2011)
Thesis (M.N.S., Nursing Science)--Prince of Songkla University, 2009